What Do You Mean Your Staff Is Like Family? - Cranston, Jerome (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
This article explores the potential for critical discourse analysis to provide insight into the language principals use to describe the adult relationships within schools. Unpacking the discourses of leadership may shed some light on how language strategically shapes the thoughts and actions of principals. In particular, the invoking of “family” to conceptualize staff relations is analyzed from a critical discourse analysis approach. Drawing on this analysis, the author offers cautions regarding how such poignant metaphors can serve as control strategies for sanctioning teacher behaviour.